Pre-occupied spaces remapping Italy's transnational migrations and colonial legacies - Fiore, Teresa (Book collections on Project MUSE., 2017)
"This book rethinks Italy's formation and development on a trans-national map through cultural analysis of travel, living and work spaces as depicted in literary, filmic and musical texts. By demonstrating how today's immigration in Italy is pre-occupied by its past emigration and colonialism, the book stresses commonalities and dispels preoccupations"--